Inflammatory functional iron deficiency common in myelofibrosis, contributes to anaemia and impairs quality of life. From the Nordic MPN study Group. (1st January 2019) - Birgegard, Gunnar; Samuelsson, Jan; Ahlstrand, Erik; Ejerblad, Elisabeth; Enevold, Christian; Ghanima, Waleed; Hasselbalch, Hans; Nielsen, Claus H.; Knutsen, Håvar; Pedersen, Ole B.; Sørensen, Anders; Andreasson, Björn
Abstract: Objectives: The study investigates the hypothesis that inflammation in myelofibrosis (MF) like in myeloma and lymphoma, may disturb iron distribution and contribute to anaemia. Methods: A cross‐sectional study of 80 MF and 23 ET patients was performed. Results: About 35% of anaemic MF patients had functional iron deficiency (FID) with transferrin saturation <20 and normal or elevated S‐ferritin (<500 µg/L). In ET, FID was rare. In MF patients with FID, 70.6% were anaemic, vs 29.4% in patients without FID ( P = 0.03). Hepcidin was significantly higher in MF patients with anaemia, including transfusion‐dependent patients, 50.6 vs 24.4 µg/L ( P = 0.01). There was a significant negative correlation between Hb and inflammatory markers in all MF patients: IL‐2, IL‐6 and TNF‐α, ( P < 0.01‐0.03), LD ( P = 0.004) and hepcidin ( P = 0.03). These correlations were also seen in the subgroup of anaemic MF patients (Table3 ). Tsat correlated negatively with CRP ( P < 0.001). Symptom burden was heavier in MF patients with FID, and MPN‐SAF quality of life scores correlated with IL‐6 and CRP. Conclusions: The inflammatory state of MF disturbs iron turnover, FID is common and contributes to anaemia development and impairment of QoL. Anaemic MF patients should be screened for FID.